Impact of outbreak COVID-19 pandemic on psychiatry emergencies in Spain. (January 2021) - Rodriguez-Jimenez, R.; Rentero, D.; Romero-Ferreiro, V.; García-Fernández, L.
Highlights: Psychiatric emergencies were lower during the COVID-19 period compared to 2019. During COVID-19 more schizo psychotic patients were attended in the emergency. During COVID-19 fewer anxiety/adaptive patients were attended in the emergency. A lower discharge/emergency ratio was observed during the COVID-19 outbreak. A higher referral to Internal Medicine ratio was observed during the COVID-19 outbreak. Abstract: The SARS-CoV-2 pandemic has caused an unprecedented clinical situation. A retrospective cross-sectional study was designed with the aim to evaluate psychiatric emergencies from March 14 to May 1, 2020, coinciding with the start of the emergency state and the lockdown until the attenuation of the confinement. Data obtained during this period were compared with the emergencies attended in the same period of 2019. A total of 213 psychiatric emergencies were attended in 2020 compared with 367 in 2019. The mean number of emergencies per day was significantly lower during the COVID-19 outbreak in 2020 (M=4.35, SD= 2.04) vs. the same period in 2019 (M=7.50, SD= 3.18). A higher percentage of patients with schizo/psychotic disorders (34.3% in 2020, vs. 24.3% in 2019), as well as a lower percentage of patients with anxiety/adaptive disorders (25.4% in 2020 vs. 35.4% in 2019) was observed during the outbreak. A significant lower mean discharge/emergency ratio (M=42.17, SD= 26.94 in 2020 vs. M=63.43, SD= 17.64 in 2019) and a higher referral to Internal Medicine/emergency ratio (M=20.55, SD= 22.16 in 2020 vs. M=3.32, SD= 6.63 in 2019) was observed. The results suggest important changes in psychiatric emergencies during the most critical period of the COVID-19 outbreak in Spain.